2022
DOI: 10.3390/ma15062173
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Gamma Radiation Transmission Rate of Heavyweight Concrete Containing Barite Aggregates

Abstract: The primary objective of this research was to study the transmission of gamma radiation from heavyweight concrete containing barite aggregates. For this purpose, cylindrical and cubic specimens were produced for 10 mix designs. The mix designs containing different percentages of barite aggregates were calculated; five mix designs were also calculated for the compressive strength of 25 MPa, while five of them were designed for the compressive strength of 35 MPa to study the influence of the compressive strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…High density concrete provides resistance towards radiation (having high linear attenuation coefficient) and is used in nuclear powerplants and reactors [ 8 , 12 ]. The reduction in the gamma transmission rate is significantly dependent on the density of concrete [ 13 ]. The density of normal-weight concrete is approximately 2400 kg/m 3 and of high-density concrete >2900 kg/m 3 , which can be obtained using heavyweight aggregates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High density concrete provides resistance towards radiation (having high linear attenuation coefficient) and is used in nuclear powerplants and reactors [ 8 , 12 ]. The reduction in the gamma transmission rate is significantly dependent on the density of concrete [ 13 ]. The density of normal-weight concrete is approximately 2400 kg/m 3 and of high-density concrete >2900 kg/m 3 , which can be obtained using heavyweight aggregates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is the most popular material used for radiation shielding due to low costs, global availability of its constituents, sufficient durability and its ability to form any shape required [ 1 , 2 ]. Moreover, the properties of cement-based composites can be easily altered by the introduction of various heavyweight fine and coarse materials [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Te results showed that increasing the ratio of barite aggregates decreased compressive strength and tensile strength. Also, the reduction of the gamma transmission rate signifcantly depends on the density of concrete [22].…”
Section: Introductionmentioning
confidence: 99%